Assessment of Heavy Metal Concentrations in Vegetables and Different Soil Types in the Kluang-Kota Tinggi Area, Johor, Malaysia - Bokhari, Juliana (2006)
The vegetables in Johore are grown on several soil types. Heavy metal contents in Johore soils and vegetables have not been fully studied although it is known that the concentration of heavy metals in soils under vegetable cultivation was affected by excessive use of fertilizers, agrochemical and addition of chicken dung. The quality of these vegetables and the soils from heavy metals perspective is important lately. The knowledge of both the total concentration and chemical speciation is necessary to understand the behavior of heavy metals in soil. This study was conducted to determine heavy metal contents in organic and mineral soils cultivated with vegetables and the relationship between heavy metal concentration and some physico-chemical properties. Heavy metal speciation study is also necessary for evaluating the mobility and bioavailability of heavy metals in the soils. Soil and vegetable samples were collected from several vegetable plots in Kluang and Kota Tinggi. A total of 177 soil samples were collected comprising of 42 organic soil samples, 81 Rengam series, 27 Telemong series and 27 Batang Merbau series soil. The soil samples were taken from 3 depths (0-20 cm, 20-40 cm and 40-60 cm) using a stainless steel auger. Top soil samples (0-20 cm) from the surrounding area, werealso collected in order to determine the background values of heavy metals in the soil as compared to the vegetable cultivated areas. GPS reading was taken at every sampling point. The crops selected were leafy vegetables (39 samples) and fruit vegetables (17 samples).